2017
DOI: 10.1021/acsphotonics.6b00994
|View full text |Cite
|
Sign up to set email alerts
|

Highly Photoluminescent Nonconjugated Polymers for Single-Layer Light Emitting Diodes

Abstract: The design, synthesis, and characterization of solution-processable polymers for organic light emitting diode (OLED) applications are presented. Theoretical calculations were employed to identify a carbazole-pyrimidine based building block as an optimized host material for the emissive layer of an idealized OLED stack. Efficient, free radical homopolymerization and copolymerization with a novel methacrylate-based heteroleptic iridium(III) complex leads to a library of nonconjugated polymers with pendant semico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 52 publications
(68 reference statements)
2
23
0
Order By: Relevance
“…9). 35 They found that the PLQYs of the polymer neat films decreased with increasing Ir(ppy) 3 phosphor concentrations (0.5-29 mol.%), suggesting the presence of undesirable interchromophore interactions in the film when the phosphor content became more concentrated, which is consistent with the observations reported in the aforementioned studies. 27,29,31 Although the copolymer with 0.5 mol.% Ir(ppy) 3 phosphor exhibited the best PLQY of 81% among the series, a minimum of 3 mol.% phosphor was required to complete the energy transfer from the host to the dopant.…”
Section: Recent Advances In Non-conjugated Polymers For Pled Applicatsupporting
confidence: 80%
“…9). 35 They found that the PLQYs of the polymer neat films decreased with increasing Ir(ppy) 3 phosphor concentrations (0.5-29 mol.%), suggesting the presence of undesirable interchromophore interactions in the film when the phosphor content became more concentrated, which is consistent with the observations reported in the aforementioned studies. 27,29,31 Although the copolymer with 0.5 mol.% Ir(ppy) 3 phosphor exhibited the best PLQY of 81% among the series, a minimum of 3 mol.% phosphor was required to complete the energy transfer from the host to the dopant.…”
Section: Recent Advances In Non-conjugated Polymers For Pled Applicatsupporting
confidence: 80%
“…This may be of particular use if the corresponding acrylic monomers required would exhibit markedly different kinetics if polymerized together, resulting in gradient, rather than random, copolymers. Indeed, polymeric materials with donor‐acceptor side‐chains have recently been used as emissive materials for OLEDs and as components of resistive memory …”
Section: Resultsmentioning
confidence: 99%
“…In general, polymer metallocomplexes are an attractive solution, as they uniquely combine the advantages of small-molecular complexes with polymers’ superior film-forming properties and excellent thermal and chemical stability. Polymers containing iridium complexes, either along the main chain or as pendant groups, have been developed, mainly with the involvement of tris-bidentate complexes, affording polymeric metallocomplexes with a variety of emission colors [ 34 , 35 , 36 , 37 , 38 , 39 ]. However, bis-tridentate polymeric metallocomplexes are scarcer in the literature.…”
Section: Introductionmentioning
confidence: 99%